Advancing cyber and information security cooperation in ASEAN - Muhammad Faizal Bin Abdul Rahman (2023)
The security of the cyber and information space is essential to the digitalisation ambitions of the ASEAN countries. ASEAN must keep abreast of a threat landscape where malicious cyber and information operations are constantly evolving. MUHAMMAD FAIZAL notes that, in two specific areas of threat, synergies can arise by coordinating the efforts undertaken by various ASEAN mechanisms such as the ASEAN Digital Ministers’ Meeting and the ASEAN Defence Ministers’ Meeting.